Can MS excel help finance students to excel? A study in student work readiness - Kirsten, E.; van Hoepen, R.; du Toit, E. (South African Journal of Higher Education, 2025)
Microsoft Excel is vital in the finance sector, and preparing students for the professional arena involves honing their spreadsheet skills. A study investigated the efficacy of a finance-centric Microsoft Excel workshop as an intervention to enhance students’ skills and readiness for work. Pre- and post-intervention tests assessed students’ perceptions and abilities. The results revealed a significant improvement across basic, intermediate, and advanced Excel skills, positively impacting students’ self-perceptions. The majority recognized Excel as a critical job market skill. The study recommends integrating Excel assignments into finance modules to elevate skills and enhance finance knowledge retention, promoting self-directed learning.